Impactos socioeconômicos causados pelo auxílio emergencial: uma análise na renda dos beneficiários do Estado do Maranhão em 2020 - SILVA, Fábio José Vieira da (2023)
This dissertation aims to analyze the impact of Emergency Aid on the pandemic crisis in the year 2020. This public policy is a consequence of the economic crisis, resulting from social distancing, caused by the growth of the lethality rate of Sars-cov-2 in all regions of the country. This fact led the Federal Government to take control measures and one of them was the creation of the cash transfer program in the pandemic. For the methodology, theoretical and empirical parts were used. In the theoretical part, it addressed a review of the literature regarding the covid-19 crisis in 2020. For the empirical methodology, it sought to collect and organize the data using descriptive statistics. The methodology applied in the research was Pearson's correlation to verify if the variables are correlated with each other. The main results found were the existence of the relationship between Emergency Aid, the number of new deaths and the eligible population in the State of Maranhão (MA), however, using the significance levels of 1% these correlations were not significant, and only the relationship between eligible people and Emergency Aid was considered significant. The plausible explanation for this result is due to the non-normality of the data due to the small sample of the period and the variability of the data. However, in a theoretical way and graphical analysis it is possible to visualize this relationship between the variables, thus verifying the importance of public policies in maintaining the income of less favored families.